Pulses for Sustainability: Breaking Agriculture and Food Sectors Out of Lock-In - Magrini, Marie-Benoit; Anton, Marc; Chardigny, Jean-Michel; Duc, Gerard; Duru, Michel; Jeuffroy, Marie-Helene; Meynard, Jean-Marc; Micard, Valerie; Walrand, Stephane (Frontiers in Sustainable Food Systems, 2018)
Crop diversification can improve the sustainability of Western agriculture. In particular, pulses are crops that can help both agriculture and the food industry become more ecological, as they reduce greenhouse gas emissions and help reduce animal-based consumption. Today, however, the development of these crops in Europe has been hindered due to lock-in, since major crops have been co-developed to a greater extent in farming and food systems. After briefly reviewing the major mechanisms that lead to this lock-in, this article adopts a co-evolution framework to address the interconnected transition of agriculture and food systems. We explore how current societal trends in the agrifood system offer new opportunities for pulses, and how simultaneous changes both in production and consumption can facilitate this dual transition. Drawing on insights from the literature and interviews with stakeholders in France—taken here as examples—we argue that to develop pulses, strong support is required from public institutions to coordinate and guide the multiple actors involved in the same direction.